IMF Staff papers : Volume 29 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1982)
This paper examines the effects of the emergence of the United Kingdom as a major oil producer, together with the pursuit of firm financial policies as part of an anti-inflation strategy, has had on the UK economy and, in particular, on the real exchange rate of the pound sterling, which appreciated by 45 percent between 1977 and late 1981. The build-up of North Sea oil production and the rise in the real price of oil have led to a significant change in the structure of the UK economy. A small dynamic macro model of the United Kingdom has been constructed to assess the quantitative importance of North Sea oil production on the economy as well as the main effects of the anti-inflation strategy. The results indicate that both direct and indirect effects of oil production on the real exchange rate and, consequently, on the manufacturing sector are large. The results also indicate that a policy of financial restraint would be successful in reducing inflation, although its costs in the short term would be high, largely because inflation expectations do not appear to adjust rapidly.